A FLASHCARD JOURNEY: - Nurul Hidayah; Hanina Syarifah; Paulina Besty Fortinasari; Siti Nur Aisyah; Wigati Sunarsih; Fadhia Bimala Nur Insani; Sinta Ria (Language and Education Journal, 2024)
Teaching English as a foreign language can be said to transform the best knowledge of acquired language from the teacher to the students. This study investigates the transformative impact of using flashcards in English language learning at SDN Potrobangsan 3, under the guidance of an English teacher in Magelang. This study uses a descriptive qualitative method with data collection by interviewing an English teacher at SDN Potrobangsan 3. The innovative use of flashcards triggers students' enthusiasm for English learning activities. Using clear and engaging visual aids, these flashcards improve various aspects of vocabulary acquisition, listening comprehension, and oral communication skills. Flashcards transform passive listeners into active participants in decoding language. In addition to improving listening skills, flashcards act as a confidence booster in verbal communication. The English teacher becomes a stage where each flashcard fosters engagement, participation, and a passion for learning. The genuine enthusiasm of the students, coupled with the passion of the teacher, weaves a creative and meaningful teaching and learning activity at SDN Potrobangsan 3.